Longitudinal displacements of railway jointless track due to local temperature difference on its length - Bednarek, Włodzimierz (Przegląd Komunikacyjny)
In the paper is shown an analysis of a CWR track’s longitudinal displacements due to a local temperature difference on its length. The thermical forces on the railway track length arise due to a local temperature difference of rail, causing the local, zonal the longitudinal displacements of rail cross-sections. Axial displacements of track induce in succession a longitudinal reaction of roadbed in such a degree on which a arising displacements allow. Additionally a arising during track operating a variable longitudinal resistance on track’s length (generated among other things by different state of ballast compaction, different pressure force of rail foot to divider), periodical acting force from vehicles, different value of adhesion wheels with rails and also different stage of rail heating, cause a disturbance section of equilibrium state of CWR track. In certain cases it assumes a shape of rails micro displacements, which can take a form e.g. creep displacements leading to value changes of longitudinal forces on this segment length with arising displacements. In paper analytical form of considered problem is given and computational examples, diagrams and tables reflecting influence of analyzed parameters on obtained a CWR track’s longitudinal displacements due to local temperature difference on its length is inserted Keywords: CWR track; Longitudinal displacement; Local temperature difference